Consequences of the 1858 Malay-Cham rebellion in Cambodia - Musa Mohamad Zain, Nik Abdul Rahman Nik Hassan Shuhaimi, Ramli Zuliskandar, Jusoh Adnan, (N/A, 2013)
Consequences of the 1858 Malay-Cham rebellion in Cambodia by Musa Mohamad Zain, Nik Abdul Rahman Nik Hassan Shuhaimi, Ramli Zuliskandar, Jusoh Adnan,